Versprechen und Verzeihen Zwei Grundbegriffe unseres ethischen Selbstverständnisses - Seibert, Christoph (Zeitschrift für Theologie und Kirche, 2012)
The article develops the thesis, that the acts of promising and forgiving play an essential part in the constitution and stabilization of human sociality. In studying the phenomena of promising and forgiving the analysis explores their far reaching anthropological and finally theological meanings. As a result a differentiated concept of these two acts is presented. In doing so the argument develops with referenee to the positions of Hume, Kant, Arendt and Rieoeur.